Septin-driven Coordination of Actin and Microtubule Remodeling Regulates the Collateral Branching of Axons - Hu, Jianli (2012)
Axon branching is fundamental to the development of the peripheral and central nervous system [1, 2]. Branches that sprout from the axon shaft are termed collateral or interstitial branches [3, 4]. Collateral branching of axons requires the formation of filopodia from actin microfilaments (F-actin) and their engorgement with microtubules (MTs) that splay from the axon shaft [4–6]. The mechanisms that drive and coordinate the remodeling of actin and MTs during branch morphogenesis are poorly understood. Septins comprise a family of GTP-binding proteins that oligomerize into higher order structures, which associate with membranes and the actin and microtubule cytoskeleton [7, 8]. Here, we show that collateral branching of axons requires SEPT6 and SEPT7, two interacting septins [9]. In the axons of sensory neurons, both SEPT6 and SEPT7 accumulate at incipient sites of filopodia formation. We show that SEPT6 localizes to axonal patches of F-actin and increases the recruitment of cortactin, a regulator of Arp2/3-mediated actin polymerization, triggering the emergence of filopodia. Conversely, SEPT7 promotes the entry of axonal MTs into filopodia, enabling the formation of collateral branches. Surprisingly, septins provide a novel mechanism for the collateral branching of axons by coordinating the remodeling of the actin and microtubule cytoskeleton.